Selected Plant Extract in Inhibiting the Growth of Bacteria Isolated from Raw Vegetables - Junar Sebua Cano (Journal of Science and Science Education, 2021)
In recent years, there has been a gradual revival of interest in the use of plant extract due to the wide spread belief that green plant sources are healthier and safer than the synthetic ones. Hence, the present study was carried out to evaluate the inhibitory effects of the ethanolic extract of Hibiscus rosa-sinensis (Gumamela) flower, Psidium guajava (Guava) leaf, Moringa oleifera (Malunggay) leaf, and Allium sativum (Garlic) clove on the microbial isolates from Brassica oleraceae (Cabbage), Brassica rapa (Pechay), and Cucumis sativus (Cucumber) using agar well diffusion method. Experimental research design was employed in the study. The 75%, 50%, and 25% concentrations of the extract were used as the treatments, while sodium hypochlorite and sterile distilled water were used as the positive and negative controls, respectively. Based on the results, the plant extract showed significant difference (p<0.05 and p<0.0) in inhibiting the growth of bacterial isolates. The 75% concentration of H. rosa-sinensis flower extract, and the 75%, 50%, and 25% concentrations of P. guajava leaf extract were found to inhibit the growth of bacterial isolates on raw vegetables, and their antimicrobial activities differed significantly (p< 0.05). On the other hand, M. oleifera leaf and A. sativum clove extract were found not effective in inhibiting the growth of bacteria on raw vegetables.